Dealing with the multidimensionality of sustainability through the use of multiple perspectives – a theoretical framework. (3rd May 2016) - Lönngren, Johanna; Svanström, Magdalena; Ingerman, Åke; Holmberg, John
Abstract : The concept of perspectives is important in discussions about the multidimensionality of sustainability problems and the need to consider many different aspects when dealing with them. This paper aims to facilitate discussions among both educators and researchers about didactical approaches to developing students' abilities to deal with the multidimensionality of sustainability challenges through the use of multiple perspectives. For this purpose, a theoretical framework was developed that describes perspectives in terms of a set of general characteristics, as well as a number of ways in which students can develop and reflect on perspectives. Development of the framework was supported by a qualitative content analysis of transcripts from interviews with undergraduate engineering students in Sweden.